Akumulasi Logam Berat Pada Kerang Hijau di Perairan Pesisir Jawa - Ariani Andayani; Isti Koesharyani; Ulfa Fayumi; Rasidi; Ketut Sugama (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Heavy Metal Accumulation on Green Mussels in the Java Coastal Water.In many countries, green mussel (Pernaviridis) is harvested as food source. It is also commonly used as indicators for toxic contaminant, i.e. heavy metals, in the coastal waters. In Indonesia, green mussels are mostly cultivated in the north coast of Java where most industrial estates are located. Without further treatment, toxic contaminant of industrial waste may give impact to the surrounding environment, not to mention the adjacent coastal waters. This study was aimed to determine the accumulation of heavy metals, namely Hg, Pb and Cd, in green mussels. Green mussel samples were collected in 2017, taken from four culture sites in the north coast of Java: Panimbang, Jakarta Bay, Brebes and Cirebon. Our results showed that the concentration of Hg, Pb and Cd in green mussel tissues of those locations are: Panimbang = Hg: <0.22 mg/kg, Pb: undetectable, and Cd: 0.068 mg/kg; Teluk Jakarta = Hg: 11.7 mg/kg, Pb: 29.4 mg/kg, and Cd: 0.42 mg/kg; Brebes = Hg: 0.01 mg/kg, Pb: 3.52 mg/kg, and Cd: 0.4 mg/kg; and Cirebon = Hg: 0.01 mg/kg, Pb: 2.66 mg/kg, and Cd: 0.73 mg/kg. These results indicate that only green mussels from Panimbang contain heavy metals below the thresholds allowed to be consumed by humansgreen musselsgreen mussels